Organic sulfur small-molecule compound for lithium-sulfur battery positive electrode material and preparation method and application of organic sulfur small-molecule compound
By designing organic sulfur small-molecule compounds containing aldehyde groups and halogen-substituted benzene derivatives and optimizing their structure, the problems of poor conductivity and the "shuttle effect" of traditional lithium-sulfur batteries are solved, and the high energy density and cycling stability are improved.
Patent Information
- Application Number
- CN202510369087.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
The poor conductivity of the single sulfur element of the positive electrode material of traditional lithium-sulfur battery, the "shuttle effect" of polysulfides, and volume expansion, limits its practical application performance.
Design a small-molecule organic sulfur compound based on aldehyde group and halogen-substituted benzene derivative, optimize its structure through molecular engineering, and improve redox activity, electronic conductivity and structural stability.
The high energy density, cycle stability and rate performance of lithium-sulfur batteries have been improved. The 1C discharge specific capacity can reach 500mAh/g, and the capacity retention rate is 80%.
Smart Images

Figure CN119874581A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-sulfur battery positive electrode materials, and in particular relates to an organic sulfur small molecule compound used for lithium-sulfur battery positive electrode materials and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices and electric vehicles due to their high energy density. However, the energy density of traditional lithium-ion batteries has approached the theoretical limit and is difficult to meet the growing energy demand. Lithium-sulfur batteries use elemental sulfur (S8) as the positive electrode material, with a theoretical specific capacity of up to 1675 mAh / g and huge energy density potential, and are considered to be the ideal choice for the next generation of high energy density energy storage devices.
[0003] However, the conventional lithium-sulfur battery cathode uses elemental sulfur (S8) which has the following inherent defects, which seriously hinders its practical application: Sulfur has poor conductivity: Elemental sulfur is essentially an insulator, which leads to low electronic conductivity of the electrode, limited utilization of active materials, and poor rate performance.
[0004] Polysulfide "shuttle effect": During the charge and discharge process, the sulfur cathode will produce soluble polysulfide intermediates (Li2S x , 4≤x≤8), these polysulfides are easily soluble in common electrolytes and shuttle between the positive and negative electrodes, leading to problems such as loss of active substances, decreased sulfur utilization at the positive electrode, corrosion of the negative electrode, reduced Coulomb efficiency and cycle life attenuation, which is the "shuttle effect".
[0005] Volume expansion: Sulfur undergoes significant volume changes during the charge and discharge process, resulting in unstable electrode structure, shedding of active materials, and affecting the cycle life of the battery.
[0006] To solve the above problems, researchers are committed to developing new cathode materials for lithium-sulfur batteries. As an important sulfur cathode material, organic sulfur compounds have attracted much attention because they can fix sulfur atoms in the organic molecular framework through covalent bonds, thereby inhibiting the dissolution and "shuttle effect" of polysulfides to a certain extent. However, existing organic sulfur small molecule cathode materials still face problems such as low capacity and insufficient cycle stability. Their performance is still limited by the length of the sulfur chain, molecular conductivity, redox activity, and compatibility with the electrolyte.
[0007] Therefore, it is urgent to develop new organic sulfur small molecule positive electrode materials with controllable structure and excellent performance to improve the comprehensive electrochemical performance of lithium-sulfur batteries. Summary of the invention
[0008] In view of this, the purpose of the present invention is to overcome the problems existing in the prior art and provide an organic sulfur small molecule compound for lithium sulfur battery positive electrode material and its preparation method and application. The compound is a new type of organic sulfur small molecule compound designed based on aldehyde-containing and halogen-substituted benzene derivatives, and the application of the compound as a positive electrode material for all-solid-state lithium sulfur batteries. The present invention aims to optimize the structure of organic sulfur small molecules through molecular engineering strategies, improve their redox activity, electronic conductivity and structural stability, thereby improving the energy density, cycle stability and rate performance of lithium sulfur batteries.
[0009] The present invention is based on an organic sulfur small molecule positive electrode material containing aldehyde groups and halogen-substituted benzene derivatives and its application in an all-solid-state lithium-sulfur battery. The 1C discharge specific capacity can reach 500mAh / g and the capacity retention rate is 80%.
[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows: <First aspect> The present invention designs an organic sulfur small molecule compound for lithium sulfur battery positive electrode material, and its general structural formula is: Ar-S n -Ar; Wherein, Ar is a fluorobenzaldehyde group; n is the number of sulfur atoms, which is 3 or 4.
[0011] Preferably, the fluorobenzaldehyde group includes one of 2-fluorobenzaldehyde group (o-fluorobenzaldehyde), 3-fluorobenzaldehyde group (m-fluorobenzaldehyde) or 4-fluorobenzaldehyde group (p-fluorobenzaldehyde). In the organic sulfur small molecule compound, Ar is a substituted phenyl group, and the substituted phenyl group is simultaneously connected with only one aldehyde group (-CHO) and one fluorine atom (-F) as a substituent.
[0012] Ar is preferably 4-fluorobenzaldehyde (p-fluorobenzaldehyde). When n is 4, the organic sulfur small molecule compound is bis(4-fluorobenzaldehyde) tetrasulfide (BFBTS for short), and the structural formula is F-C6H3(CHO)-S4-C6H3(CHO)-F.
[0013] The number of sulfur atoms n of the present invention is 3 or 4, which has a higher energy density of sulfur batteries. The energy storage capacity of sulfur-based positive electrode materials mainly comes from the redox reaction of sulfur elements, and the length of the sulfur chain directly determines the number of sulfur atoms in each organic sulfur molecule. When the value of n is too small (less than 3), it means that the number of sulfur atoms contained in each organic sulfur small molecule is significantly reduced. The reduction in the number of atoms directly leads to a decrease in the content of active sulfur, thereby reducing the theoretical specific capacity of the positive electrode material. Although the molecular weight of the organic sulfur compound will also decrease with the decrease in the length of the sulfur chain, the reduction in capacity usually exceeds the reduction in molecular weight, so the overall energy density will be adversely affected. In addition, the length of the sulfur chain affects the redox reaction activity of sulfur to a certain extent. Although the organic sulfur compound is intended to improve the insulation of elemental sulfur, a too short sulfur chain may not be able to fully exert the redox potential of sulfur, resulting in insufficient redox reaction of sulfur or changes in the reaction mechanism, reducing the utilization rate of sulfur, and further reducing the actual discharge capacity. The present invention emphasizes the enhancement of redox activity by introducing aldehyde and halogen substituents, but if the sulfur chain itself is too short, even with the assistance of the substituent, it may be difficult to achieve the ideal capacity level.
[0014] The present invention preferably controls the sulfur chain length to be 3-4, aiming to balance the capacity and polysulfide solubility. Too short a sulfur chain length (n<3) may change the electronic structure and chemical properties of the sulfur chain, which may affect the stability of the sulfur chain. Although short sulfur chains may theoretically reduce the generation of long-chain polysulfides (the main substance causing the shuttle effect), too short a sulfur chain may form other types of soluble sulfur species, and there may still be problems with dissolution and migration.
[0015] <Second Aspect> The present invention also provides a method for preparing the organic sulfur small molecule compound, comprising the following steps: Fluorobenzaldehyde and Na2S n Add it into a polar solvent, heat it to 80-100°C, stir and react for 12-24 hours, pour the reaction mixture into an anti-solvent, and the resulting precipitated product is an organic sulfur small molecule compound.
[0016] Preferably, the fluorobenzaldehyde is one of 2-fluorobenzaldehyde (o-fluorobenzaldehyde), 3-fluorobenzaldehyde (m-fluorobenzaldehyde) or 4-fluorobenzaldehyde (p-fluorobenzaldehyde).
[0017] Preferably, Na2S n The value of n in is 3 or 4.
[0018] Preferably, fluorobenzaldehyde and Na2S n The molar ratio of fluorobenzaldehyde and Na2S is 1:1.1-1.5, preferably 1:1.2. n, the dosage ratio of polar solvent is 1 mol:1.1-1.5 mol:80-120ml.
[0019] Preferably, the polar solvent comprises N,N-dimethylformamide (DMF).
[0020] Preferably, the reaction is carried out under nitrogen protection. The reaction system is heated to 80-100°C and stirred for 12-24 hours. After the reaction is completed, it is cooled to room temperature. The main purpose of cooling to room temperature is to terminate the reaction and prepare for the subsequent precipitation step. At this time, the system is mainly in the state of solution or suspension, and a large amount of precipitation product will not be obtained.
[0021] Preferably, the anti-solvent is deionized water. Deionized water as an anti-solvent can effectively induce BFBTS to precipitate in large quantities and efficiently from the DMF solution and improve the purity of the product.
[0022] Preferably, the obtained precipitated product is centrifuged to collect a solid product, which is an organic sulfur small molecule compound. The solid product after centrifugation is washed 2-3 times with deionized water and ethanol respectively to remove residual reactants and solvents. The washed product is placed in a vacuum drying oven and vacuum dried at 50-70° C. for 10-15 hours to obtain the target product.
[0023] Fluorobenzaldehyde is 4-fluorobenzaldehyde, Na2S n is Na2S4, and the obtained product is bis(4-fluorobenzaldehyde) tetrasulfide (BFBTS).
[0024] <Third Aspect> The present invention also provides an application of the organic sulfur small molecule compound in preparing a positive electrode of a lithium ion battery.
[0025] The positive electrode of the lithium-ion battery includes an organic sulfur small molecule compound, a conductive additive, and a binder, wherein the mass ratio of the organic sulfur small molecule compound, the conductive additive, and the binder is 7:2:1.
[0026] The conductive additive is selected from one or more of carbon black, acetylene black, graphene, and carbon nanotubes.
[0027] The binder is selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and sodium carboxymethyl cellulose (CMC).
[0028] Preparation method of lithium-ion battery positive electrode: grind and mix the organic sulfur small molecule compound and the conductive additive evenly, add them to the binder / NMP solution, continue grinding and stirring to make a uniform positive electrode slurry, and then evenly coat the positive electrode slurry and vacuum dry it.
[0029] The present invention also provides an application of the organic sulfur small molecule compound in an all-solid-state lithium-sulfur secondary battery.
[0030] The present invention also provides an all-solid-state lithium-sulfur secondary battery, comprising a sulfide solid electrolyte, a negative electrode and a lithium-ion battery positive electrode prepared from the above-mentioned organic sulfur small molecule compound.
[0031] The negative electrode includes a lithium metal negative electrode or a metal lithium composite negative electrode.
[0032] The sulfide solid electrolyte includes sulfide electrolytes including Li6PS5Cl, Li3PS4, Li 10 GeP2S 12 , Li6PS5Br, Li6PS5I.
[0033] The present invention achieves high energy density and more stable cycle performance through molecular structure design, and has better battery performance. The capacity of traditional organic sulfur positive electrode materials is limited, and the present application effectively improves the redox activity and utilization rate of sulfur by introducing aldehyde groups and halogen substituents, thereby making it possible to achieve higher energy density and meet high energy requirements. The more stable molecular structure formed by the introduction of halogen substituents may inhibit the dissolution of polysulfides and the occurrence of shuttle effects, and enhance the structural stability of electrode materials, thereby improving the cycle life of the battery.
[0034] Compared with the all-solid-state lithium metal battery in the prior art, the beneficial effects of the present invention are: (1) High capacity and stable sulfur chain: By precisely controlling the length of the sulfur chain (n=3, 4), the generation of long-chain polysulfides is effectively reduced, thereby inhibiting the "shuttle effect" of polysulfides to a certain extent and improving the stability of the sulfur chain. At the same time, the four-sulfur chain structure can provide a higher theoretical capacity. According to calculations, the theoretical specific capacity of BFBTS can reach more than 714mAh / g.
[0035] (2) The redox activity enhancement effect of the aldehyde group: The aldehyde group (-CHO) introduced into the molecular structure acts as an electron-withdrawing group, which can effectively adjust the overall electronic structure of the molecule, enhance the redox activity of the molecule, and reduce the energy barrier of the sulfur redox reaction, thereby improving the utilization rate of sulfur and increasing the actual capacity of the battery.
[0036] (3) Synergistic effect of halogen substituents: The fluorine atom (F) introduced into the molecular structure has strong electronegativity, which can stabilize the sulfur chain and enhance the strength of the intramolecular covalent bond, thereby reducing the solubility of organic sulfur small molecules in the electrolyte and further inhibiting the generation and diffusion of polysulfides.
[0037] (4) Molecular design optimization to improve conductivity: The conjugated structure of the benzene ring and the introduction of aldehyde and halogen substituents have improved the electronic conductivity of the material to a certain extent, reduced electrode polarization, and are beneficial to improving the rate performance and energy efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 The cycle performance curve of BFBTS prepared in Example 1 in a lithium-sulfur battery; Figure 2 The figure is a comparison of the cycle performance of Example 1 and Comparative Example 2 in a lithium-sulfur battery; Figure 3 is the mass spectrum of Example 1; Figure 4 This is the mass spectrum of Example 2. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0040] Example 1 This embodiment provides the preparation of a bis(4-fluorobenzaldehyde) tetrasulfide (BFBTS) positive electrode sheet.
[0041] The preparation method of the bis(4-fluorobenzaldehyde) tetrasulfide (BFBTS) comprises the following steps: S1. Raw materials and reagents: Reagent preparation: 4-fluorobenzaldehyde (99%, Sigma-Aldrich), N,N-dimethylformamide (DMF, anhydrous, analytical grade), deionized water, anhydrous ethanol, Na2S4 (99%, Rohn's reagent).
[0042] S2. Synthesis process: 4-Fluorobenzaldehyde (12.4 g, 0.1 mol) and Na2S4 (17.4 g, 0.12 mol) were added to a 250 mL three-necked flask equipped with a magnetic stirrer. 100 mL of anhydrous N,N-dimethylformamide (DMF) was added to the flask as a solvent. The flask was placed in an oil bath, heated to 90°C under nitrogen atmosphere, and stirred for 18 hours. During the reaction, the color of the system gradually changed from light yellow to dark red. After the reaction was completed, the heating was stopped and the reaction was cooled to room temperature. The reaction mixture was poured into 500 mL of deionized water and stirred vigorously to precipitate a red solid. The red solid precipitate was collected by centrifugation, with the speed set at 4000 rpm and the centrifugation time set at 10 minutes. The collected red solid precipitate was washed 3 times with 200 mL of deionized water and 100 mL of anhydrous ethanol respectively to fully remove the residual reactants and solvents. The washed red solid product was placed in a vacuum drying oven and vacuum dried at 60°C for 12 hours to obtain a red solid product bis(4-fluorobenzaldehyde) tetrasulfide (BFBTS) with the following structural formula: .
[0043] Figure 3 This is the mass spectrum of the product of Example 1. The proportion of S is 34.25%, which is confirmed to be BFBTS.
[0044] S3. Preparation of positive electrode sheet: BFBTS material, conductive carbon black (Super P, Timcal) and polyvinylidene fluoride (PVDF, Solef5130) were weighed in a mass ratio of 7:2:1.
[0045] Add the weighed BFBTS material and conductive carbon black into an agate mortar and grind them thoroughly to mix evenly.
[0046] The PVDF binder was dissolved in 20 mL of N-methylpyrrolidone (NMP, anhydrous, 99%, Sigma-Aldrich) solvent to prepare a PVDF / NMP solution.
[0047] The uniformly ground BFBTS and carbon black mixture was gradually added to the PVDF / NMP solution, and the mixture was continuously ground and stirred to adjust the slurry viscosity to 500 mPa·s to prepare a uniform black cathode slurry.
[0048] The prepared positive electrode slurry was evenly coated on an aluminum foil current collector with a thickness of 20 μm.
[0049] The coated aluminum foil was placed in a vacuum oven and vacuum dried at 60° C. for 12 hours to fully remove the solvent NMP.
[0050] The dried electrode sheets were rolled to 50 μm using a roller press to improve the density of the electrode sheets and the contact of the materials.
[0051] The rolled electrode sheets are cut into circular electrode sheets with a diameter of 10 mm.
[0052] Example 2 This embodiment provides the preparation of a bis(4-fluorobenzaldehyde) trisulfide positive electrode sheet.
[0053] The preparation method of bis(4-fluorobenzaldehyde) trisulfide comprises the following steps: S1. Raw materials and reagents: Reagent preparation: 4-fluorobenzaldehyde (99%, Sigma-Aldrich), N,N-dimethylformamide (DMF, anhydrous, analytical grade), deionized water, anhydrous ethanol, Na2S3 (99%, Tianfu Chemical).
[0054] S2. Synthesis process: 4-Fluorobenzaldehyde (12.4 g, 0.1 mol) and Na2S3 (15.0 g, 0.12 mol) were added to a 250 mL three-necked flask equipped with a magnetic stirrer. 100 mL of anhydrous N,N-dimethylformamide (DMF) was added to the flask as a solvent. The flask was placed in an oil bath, heated to 90°C under nitrogen atmosphere, and stirred for 18 hours. During the reaction, the color of the system gradually changed from light yellow to orange-red. After the reaction was completed, the heating was stopped and the reaction was cooled to room temperature. The reaction mixture was poured into 500 mL of deionized water and stirred vigorously to precipitate an orange-red solid precipitate. The orange-red solid precipitate was collected by centrifugation, with the speed set at 4000 rpm and the centrifugation time set at 10 minutes. The collected orange-red solid precipitate was washed 3 times with 200 mL of deionized water and 100 mL of anhydrous ethanol respectively to fully remove the residual reactants and solvents. The washed orange-red solid product was placed in a vacuum drying oven and vacuum dried at 60°C for 12 hours to obtain an orange-red solid product, bis(4-fluorobenzaldehyde) trisulfide, with the following structural formula: .
[0055] Figure 4 This is the mass spectrum of Example 2. The proportion of S is 20.66%, which is confirmed to be bis(4-fluorobenzaldehyde) trisulfide.
[0056] S3. The positive electrode sheet is prepared in the same manner as in Example 1.
[0057] Example 3 This embodiment provides the preparation of a bis(2-fluorobenzaldehyde) tetrasulfide positive electrode sheet. The preparation method steps and parameters of the bis(2-fluorobenzaldehyde) tetrasulfide (BFBTS) are exactly the same as those in Example 1, except that the reagent raw material 4-fluorobenzaldehyde is replaced with 2-fluorobenzaldehyde, and the structural formula is as follows: .
[0058] Example 4 This embodiment provides the preparation of a bis(3-fluorobenzaldehyde) tetrasulfide positive electrode sheet. The preparation method steps and parameters of the bis(3-fluorobenzaldehyde) tetrasulfide (BFBTS) are exactly the same as those in Example 1, except that the reagent raw material 4-fluorobenzaldehyde is replaced with 3-fluorobenzaldehyde, and the structural formula is as follows: .
[0059] Comparative Example 1 This comparative example provides bisbenzaldehyde tetrasulfide (BBTS) prepared as a comparative material, which has a structure similar to that of BFBTS but does not contain a fluorine substituent.
[0060] The preparation method of the bisbenzaldehyde tetrasulfide (BBTS) comprises the following steps: S1. Raw materials and reagents: Reagent preparation: benzaldehyde (99%, Sigma-Aldrich), N,N-dimethylformamide (DMF, anhydrous, 99%, Sigma-Aldrich), deionized water, anhydrous ethanol, Na2S4 (99%, Rohn's reagent) S2. Synthesis process: Benzaldehyde (10.6 g, 0.1 mol) and Na2S4 (17.4 g, 0.12 mol) were added to a 250 mL three-necked flask equipped with a magnetic stirrer. 100 mL of anhydrous N,N-dimethylformamide (DMF) was added to the flask as a solvent. The flask was placed in an oil bath, heated to 90°C under nitrogen atmosphere, and stirred for 18 hours. During the reaction, the color of the system gradually changed from light yellow to brown-red. After the reaction was completed, the heating was stopped and cooled to room temperature. The reaction mixture was poured into 500 mL of deionized water and stirred vigorously to precipitate a brown-red solid precipitate. The red solid precipitate was collected by centrifugation, with the speed set at 4000 rpm and the centrifugation time set at 10 minutes. The collected brown-red solid precipitate was washed 3 times with 200 mL of deionized water and 100 mL of anhydrous ethanol respectively to fully remove the residual reactants and solvents. The washed red solid product was placed in a vacuum drying oven and vacuum dried at 60°C for 12 hours to obtain a brownish red solid product, dibenzaldehyde tetrasulfide (BBTS), with the following structural formula: .
[0061] S3 is the same as in Example 1.
[0062] Comparative Example 2 This comparative example provides a single substance S (99%, Adamas) prepared as a comparative material, and the positive electrode sheet is prepared the same as in Example 1 and Comparative Example 1.
[0063] Comparative Example 3 This comparative example provides the preparation of a bis(fluorobenzene) tetrasulfide positive electrode sheet. The preparation method steps and parameters of the bis(fluorobenzene) tetrasulfide (the molar ratio of fluorobenzene: Na2S4 is 1:1.2) are exactly the same as those in Example 1, except that the reagent raw material 4-fluorobenzaldehyde is replaced with fluorobenzene, and the structural formula is as follows: .
[0064] Comparative Example 4 This comparative example provides the preparation of a bis(4-aminobenzaldehyde) tetrasulfide positive electrode sheet. The steps and parameters of the preparation method of bis(4-aminobenzaldehyde) tetrasulfide (the molar ratio of 4-aminobenzaldehyde:Na2S4 is 1:1.2) are exactly the same as those in the embodiment, except that the reagent raw material 4-fluorobenzaldehyde is replaced by 4-aminobenzaldehyde, and the structural formula is as follows: .
[0065] As a substituent on the phenyl group, the amine group (-NH2) may have insufficient or unfavorable redox activity in the application of organic sulfur positive electrode materials compared with the preferred aldehyde group (-CHO) and fluorine atom (-F) of the present invention: Electron donation of the amine group: The amine group (-NH2) is a typical electron-donating group. Compared with the electron-withdrawing aldehyde group (-CHO) and fluorine atom (-F), the amine group increases the electron cloud density of the benzene ring. Reduce the redox potential: Electron-donating groups usually reduce the oxidation potential of molecules, making them more difficult to oxidize. The positive electrode material needs to undergo an oxidation reaction to release electrons. The introduction of the amine group may cause the redox potential of the organic sulfur molecule to be too low, making it insufficiently active within the positive electrode potential window of the lithium-sulfur battery, making it difficult to effectively participate in the electrochemical reaction, thereby reducing the utilization rate of sulfur and the battery capacity. The chemical stability may be poor, and there are compatibility issues with the electrolyte: The amine group may react adversely with the sulfide electrolyte, resulting in an increase in interfacial side reactions and affecting the battery performance. The improvement in conductivity may be limited or unfavorable. The effect of amine groups on conductivity is uncertain: although amine groups contain nitrogen atoms and may introduce a certain electronic conjugation effect, their effect on improving the conductivity of organic sulfur small molecules may not be as obvious as the synergistic effect of the benzene ring conjugated system and the electron-withdrawing group. It may even reduce conductivity: if the amine group causes the molecular structure to become more crowded or the electronic structure to change unfavorably, it may reduce the conductivity of the material.
[0066] Comparative Example 5 This comparative example provides the preparation of a bis(aniline) tetrasulfide positive electrode sheet. The steps and parameters of the preparation method of bis(phenylamine) tetrasulfide (the molar ratio of aniline: Na2S4 is 1:1.2) are exactly the same as those in the embodiment, except that the reagent raw material 4-fluorobenzaldehyde is replaced by aniline, and the structural formula is as follows: .
[0067] Comparative Example 6 This comparative example provides a method for preparing a bis(4-fluorobenzaldehyde) disulfide positive electrode sheet. This comparative example provides a method for preparing a bis(4-fluorobenzaldehyde) disulfide positive electrode sheet.
[0068] The preparation method of bis(4-fluorobenzaldehyde) disulfide comprises the following steps: S1. Raw materials and reagents: Reagent preparation: 4-fluorobenzaldehyde (99%, Sigma-Aldrich), N,N-dimethylformamide (DMF, anhydrous, analytical grade), deionized water, anhydrous ethanol, Na2S2 (99%, Tianfu Chemical).
[0069] S2. Synthesis process: 4-Fluorobenzaldehyde (12.4 g, 0.1 mol) and Na2S2 (9.4 g, 0.12 mol) were added to a 250 mL three-necked flask equipped with a magnetic stirrer. 100 mL of anhydrous N,N-dimethylformamide (DMF) was added to the flask as a solvent.
[0070] The flask was placed in an oil bath, and the temperature was raised to 90°C under nitrogen atmosphere, and stirred for 18 hours. During the reaction, the color of the system gradually changed from light yellow to yellow.
[0071] After the reaction was completed, heating was stopped and the mixture was cooled to room temperature. The reaction mixture was poured into 500 mL of deionized water and stirred vigorously to precipitate a yellow solid. The yellow solid precipitate was collected by centrifugation, the speed was set at 4000 rpm, and the centrifugation time was 10 minutes.
[0072] The collected yellow solid precipitate was washed three times with 200 mL of deionized water and 100 mL of anhydrous ethanol, respectively, to fully remove the residual reactants and solvents.
[0073] The washed yellow solid product was placed in a vacuum drying oven and vacuum dried at 60°C for 12 hours to obtain a yellow solid product bis(4-fluorobenzaldehyde) disulfide, the structural formula of which is as follows: .
[0074] S3 is the same as in Example 1.
[0075] Performance test case The products obtained in the above examples and comparative examples were assembled: in an inert gas glove box with a water and oxygen content of ≤0.01 ppm, the corresponding electrode sheet was used as the positive electrode, and 120 mg of Li6PS5Cl was weighed and pressed into a sheet with an area of 0.785 cm 2 , a 1 mm thick sheet as the electrolyte layer. The positive electrode has a unit area loading of 5 mg cm -2 The electrode is a lithium metal negative electrode layer, and an all-solid-state lithium-sulfur battery is assembled. Finally, the cyclic discharge is first charged and discharged at 0.1C for two cycles, and then a long cycle test is performed at 1C. The first efficiency is tested, and the capacity retention rate is tested after 500 cycles. The results are shown in Table 1: Table 1 Cyclic performance test
[0076] As can be seen from Table 1, the experimental results fully prove that the BFBTS material has high capacity, excellent cycle stability, good rate performance and high redox activity, and exhibits excellent comprehensive electrochemical performance as a positive electrode material for lithium-sulfur batteries. The comparative experiment further verifies the synergistic effect of halogen substituents on improving the performance of organic sulfur positive electrode materials. The cycle performance curve of BFBTS prepared in Example 1 in lithium-sulfur batteries is shown in Figure 1. Figure 1 As shown, the cycle performance of Example 1 and Comparative Example 2 in lithium-sulfur batteries is compared. Figure 2 shown.
[0077] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. An organic sulfur small molecule compound for lithium-sulfur battery positive electrode material, characterized in that: The general structural formula of organic sulfur small molecule compounds is: Ar-S n -Ar; wherein Ar is a fluorobenzaldehyde group; n is the number of sulfur atoms, which is 3 or 4.
2. The organic sulfur small molecule compound according to claim 1, characterized in that: The fluorobenzaldehyde group is one of 2-fluorobenzaldehyde group, 3-fluorobenzaldehyde group and 4-fluorobenzaldehyde group.
3. A method for preparing an organic sulfur small molecule compound as claimed in claim 1, characterized in that: The steps include: Fluorobenzaldehyde and Na2S n Add it into a polar solvent, heat it to 80-100°C, stir and react for 12-24 hours, pour the reaction mixture into an anti-solvent, and the resulting precipitated product is an organic sulfur small molecule compound.
4. The method for preparing an organic sulfur small molecule compound according to claim 3, characterized in that: Fluorobenzaldehyde is one of 2-fluorobenzaldehyde, 3-fluorobenzaldehyde and 4-fluorobenzaldehyde; and / or, Na2S n It is one of Na2S3 and Na2S4; And / or, the polar solvent includes N,N-dimethylformamide.
5. The method for preparing an organic sulfur small molecule compound according to claim 3, characterized in that: Fluorobenzaldehyde and Na2S n The molar ratio is 1:1.1-1.
5.
6. Use of the organic sulfur small molecule compound as claimed in claim 1 in preparing a positive electrode of a lithium ion battery.
7. A positive electrode for a lithium ion battery, characterized in that: It comprises the organic sulfur small molecule compound as claimed in claim 1, a conductive additive, and a binder; The conductive additive is selected from one or more of carbon black, acetylene black, graphene, and carbon nanotubes; The binder is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, and sodium carboxymethyl cellulose.
8. A method for preparing a positive electrode of a lithium ion battery as claimed in claim 7, characterized in that: The method comprises the following steps: grinding and mixing the organic sulfur small molecule compound and the conductive additive evenly, adding them into the binder / NMP solution, continuing to grind and stir to prepare the positive electrode slurry, and then coating the positive electrode slurry and vacuum drying.
9. Use of the organic sulfur small molecule compound as claimed in claim 1 in an all-solid-state lithium-sulfur secondary battery.
10. An all-solid-state lithium-sulfur secondary battery, characterized in that: The invention comprises a sulfide solid electrolyte, a negative electrode and a lithium ion battery positive electrode prepared from the organic sulfur small molecule compound as claimed in claim 1.
Citation Information
Patent Citations
Sulfur energy storage battery and method for improving rate capability and cycling stability of sulfur energy storage battery
CN112952198A
Sulfur-containing polymer, preparation method, negative pole piece, secondary battery and electric device
CN117143287A
Sulfane sulfur-selective fluorescent probe
US20180052105A1